Influence of hydrolysis rate of urea on ruminal bacterial diversity level and cellulolytic bacteria abundance in vitro - Wang, Pengpeng; Zhao, Shengguo; Nan, Xuemei; Jin, Di; Wang, Jiaqi (PeerJ, 2018)
The objective of this experiment was to evaluate the effects of urea hydrolysis rate on ruminal bacterial diversity level and cellulolytic bacteria abundance in vitro. To control urea hydrolysis rate, urea and urease inhibitor (acetohydroxamic acid, AHA) were supplemented to a 2 × 2 factorial design, with urea supplemented at 0 or 20 g/kg dry matter (DM) of substrate, and AHA equivalent to 0 or 450 mg/kg DM of substrate. Ruminal fluid was collected from three Chinese Holstein dairy cows, fed a TMR, and incubated at 39 °C for 12 h after the addition of urea and AHA. Rumen fermentation parameters, which indicated the rate of ammonia formation (including ammonia-nitrogen (NH3-N) and urea-nitrogen concentrations, urease activity, and microbial crude protein) were measured by chemical analysis. Bacterial diversity was analyzed by denaturing gradient gel electrophoresis (DGGE). Total bacteria and cellulolytic bacteria abundance was detected by quantitative PCR. Results showed that AHA addition significantly decreased the rate of ammonia formation when urea was supplemented. Urea and AHA supplementation significantly increased the bacterial community diversity level according to the Shannon–Weiner index of 16S DGGE images. Furthermore, ruminal bacterial profiles were separated by ammonia release rate when urea was supplemented, according to the DGGE and hierarchical cluster analysis. Urea supplementation reduced the abundance of cellulolytic bacteria, such as Ruminococcus albus, R. flavefaciens, Fibrobacter succinogenes, and Butyrivibrio fibrosolvens, but inhibition of urea hydrolysis by AHA addition alleviated the reductions during the early period of incubation. In conclusion, slow release of ammonia induced by urease inhibitor influenced the ruminal bacterial diversity level and lessened the inhibition of total bacteria growth at the incubation of 12 h and F. succinogenes during the early period of incubation.
Keywords: Urea; Ammonia; Acetohydroxamic acid; Cellulolytic bacteria; Bacterial community